Greco-Latin tradition in the Costa Rican novel Los Peor, by Fernando Contreras Castro - Arroyo Carvajal, Yordan (2021)
This article analyzes six grecolatin intertexts present in the Costa Rican novel Los Peor (1995), by Fernando Contreras Castro, whose main focus is on the hypotextuality of the Polyphemus’s myth from receptions with La Odisea (VIII a. C., IX), from Homer and The Metamorphoses (VIII d. C), by Ovidio. As theoretical-methodological references, the Dictionaries of symbols by Chevalier (1986) and Cirlot (1992) are used; the book The monstrous and the beautiful (1988), by Rafael Ángel Herra; and the theory of intertextuality by Julia Kristeva (1978) from a socio-critical perspective, in order to encompass this research within the reference framework of studies on classical tradition (García, 2016). Finally, as conclusions, it was found that the analyzed intertexts represent a Costa Rican environment in crisis and in transformation from migratory waves and socioeconomic spaces governed by the growth of the city at the end of the 20th century.